Mechanically Interlocked Hydrogel–Elastomer Hybrids for On‐Skin Electronics - Pan, Shaowu; Zhang, Feilong; Cai, Pingqiang; Wang, Ming; He, Ke; Luo, Yifei; Li, Zheng; Chen, Geng; Ji, Shaobo; Liu, Zhihua; Loh, Xian Jun; Chen, Xiaodong (Advanced functional materials, 2020)
Soft electronics that seamlessly interface with skin are of great interest in health monitoring and human–machine interfaces. However, achieving mechanical softness, skin adhesiveness, and high conductivity concurrently has always been a major challenge due to the difficulty in bonding dissimilar materials while retaining their respective properties. Herein, the mechanically interlocked hydrogel–elastomer hybrid is reported as a viable solution to this problem. Hydrogels with low moduli and high adhesiveness are employed as the substrate, while porous elastomer webs are used as matrices to load conductive films and lock the hydrogels through a mechanically interlocked structure. The bonding strength between the hydrogel and elastomer in the interlocking hybrid structure is 14.3 times of that obtained via the physical stacking method. As a proof of concept, interlocking hybrids are used as on‐skin electrodes for electrophysiological signal recording including electromyography and electrocardiography. The robust hybrid electrodes are able to detect signals after multiple cycles. The proposed strategy not only is an effective approach to achieve interlocking structures, but also provides a new perspective for soft and stretchable electronics. A novel hydrogel–elastomer hybrid is developed by mechanical interlocking. Porous elastomer webs are used as matrices to load conductive materials and lock hydrogels through an interlocking structure to achieve mechanically soft and skin‐adhesive electrodes. The interlocking hybrid is used as an on‐skin electrode for recording electrophysiological signals.